2021
DOI: 10.1021/acs.organomet.1c00470
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Rare-Earth Metal Alkyl Complexes Bearing a Dianionic α-Iminopyridyl Ligand and Their Catalytic Activities toward Polymerization of 2-Vinylpyridine

Abstract: The rare-earth metal alkyl complexes bearing a dianionic αiminopyridyl ligand {μ-η 2 :σ 1 :κ 1). In the process, the reactions underwent double deprotonation of the functionalized donor group 2-aminomethylpyridine. Reaction of Sc(CH 2 SiMe 3 ) 3 (THF) 2 with compound 1 in a shortened reaction time afforded the scandium dialkyl complex {2- 3f) which would slowly transform into 2f at room temperature, indicating that the formation of dianionic α-iminopyridine went through the continual deprotonation reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Wang et al. reported that rare‐earth metal alkyl complexes 46 – 51 bearing a dianionic α‐iminopyridyl ligand exhibited good catalytic activities (∼400 h −1 ) toward polymerization of 2‐VP with high iso‐selectivity ( P m ∼0.96) (Scheme 5, Table 4, Runs 5–10) [20] . Luo et al.…”
Section: Stereoselective Polymerization Of 2‐vinylpyridinementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al. reported that rare‐earth metal alkyl complexes 46 – 51 bearing a dianionic α‐iminopyridyl ligand exhibited good catalytic activities (∼400 h −1 ) toward polymerization of 2‐VP with high iso‐selectivity ( P m ∼0.96) (Scheme 5, Table 4, Runs 5–10) [20] . Luo et al.…”
Section: Stereoselective Polymerization Of 2‐vinylpyridinementioning
confidence: 99%
“…[19] Wang et al reported that rare-earth metal alkyl complexes 46-51 bearing a dianionic α-iminopyridyl ligand exhibited good catalytic activities (~400 h À 1 ) toward polymerization of 2-VP with high isoselectivity (P m ~0.96) (Scheme 5, Table 4, Runs 5-10). [20] ). [21] In 2018, Mu's group [22] reported the catalytic performance of diketiminato rare earth metal complexes 58-63 for 2-VP polymerization (Scheme 6).…”
Section: Runmentioning
confidence: 99%
“…To be noted, this fascinating copolymerization provides an ideal model to computationally simulate the competitive insertion behaviors of polar and nonpolar olefins and to elucidate the origins of specific regio- and stereoselectivity. As part of our ongoing endeavors in the mechanistic understanding of rare-earth catalysis, ,, we performed here a detailed mechanistic investigation on the model reaction of co-syndiospecific alternating copolymerization of anisylpropylene (AP) and styrene catalyzed by C 5 Me 4 SiMe 3 -ligated scandium complex ( Sc-1 ) through DFT calculations (Figure c). By comparison of various possible insertion modes, a new amino-dissociated mechanism was proposed for AP insertion at chain initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, the double deprotonation of morpholinyl-substituted 2-aminomethyl pyridine in the presence of rare-earth metal triamido/trialkyl complexes was a feasible way to anchor an α-iminopyridine moiety in the dianionic form with a novel μ- η 2 : σ 1 : κ 1 binding mode to the metal center . The absence of double deprotonation was observed if the morpholinyl group was replaced with a noncoordinating group, i.e., a tert -butyl group, emphasizing the key role of the coordinated morpholinyl moiety in the sequential deprotonation.…”
Section: Introductionmentioning
confidence: 99%